Biodegradable polymeric ion–releasing fillersWhy Is This Important? - Hannah Reynolds, BS; Bryanna Bravo, BS; Germelle Fulford, MS; Ana Martinez, BS; Mark A. Latta, MS, DMD; Stephen M. Gross, BS, PhD (JADA Foundational Science)
Background: Dentists spend considerable time treating issues stemming from caries, especially recurrent caries. European Union regulations require microplastics to be biodegradable. The goal of this research is to develop biodegradable, ion-releasing fillers that could be incorporated into dental materials that aid in remineralization of teeth. Methods: Polymeric ion–releasing fillers (PIRFs) that released calcium from a dental composite were prepared. These fillers were synthesized from a biodegradable polymer obtained from a renewable resource (alginate) and are capable of releasing calcium ions. Synthetic variables included the concentration of reactants, emulsifying agents, and applied shear rate. PIRFs were incorporated into dental formulations and categorized by scanning electron microscopy, ion release, degree of conversion, depth of cure, and viscosity measurements. Results: Scanning electron microscopic images confirmed the successful isolation of the PIRFs from synthesis and subsequent mixing into a bisphenol A glycidyl methacrylate and triethylene glycol dimethacrylate continuous phase that was converted into a dental composite. The degree of conversion and depth of cure measurements were consistent with those of a typical dental material, showing the viability of adding PIRFs to dental composites. The effect of mixing the PIRFs on the viscosity of the continuous phase was measured. The addition of up to 5 wt/wt% of these fillers did not significantly increase viscosity, allowing for inclusion into a wide array of dental materials. Incorporation led to pseudoplastic behavior, in which the viscosity decreased with increased shear rate. The incorporation of PIRFs leads to rheopectic behavior at low shear rates and thixotropic behavior at higher rates. Conclusions: Biodegradable PIRFs are a promising approach to help prevent caries.